Identification and characterization of stevia rebaudiana extraction for total phenolic compound using soxhlet extraction and microwave-assisted extraction techniques - Erna Wati, Hajar (2013)
This study focused on identifying extraction condition (e.g. sample concentration,extraction time) of total phenolic compound (TPC) from leaves, stems and flowers of Stevia rebaudiana. Two method processes were used: 1) using Soxhlet Extraction (SE)and 2) Microwave-Assisted Extraction (MAE). Possible mechanisms of productivity enhancement by both methods were investigated. The extract were analyzed with an appropriate Gas Chromatography-Mass Spectrometry (GC-MS) and Fourier Transform Infrared Spectroscopy (FTIR). The reproducibility of extraction and of chromatographic analysis was proved.The identification of extraction in both extraction technique has been intensively studied. In comparison of these two techniques to extraction of TPC in leaves, stems and flowers of Stevia rebaudiana, MAE had a higher extraction efficiency with reduces extraction time. The yield of TPC in leaves of Stevia rebaudiana was 100.385 mg GAE/g dw and in stems was 18.702 mg GAE/g dw at concentration 0.1 g/ml. Meanwhile, the yield TPC in flowers was 64.461 mg GAE/g dw at the concentration 0.06 g/ml after 12 min running using MAE.The qualitative GC-MS analysis of the extract from leaves, stems and flowers of Stevia rebaudiana showed that total ion chromatogram (TIC) of Soxhlet and MAE shows some valuable constituents of extracts such as Octadecanoic acid, nHexadecanoic acid, 1-Octadecene, Taraxasterol, Tridecanoic acid, D-allose,Morpinan, Benzene rings, Stigmasterol, β-Sitosterol, γ-Sitosterol, α-Amyrin,Longifolenaldehyde, Allo-inisitol, Neo-inositol, Azulene, and Phenol. The results suggest that Stevia rebaudiana can also be consider as a potential source of essential oil for the use of cosmeceutical, medicinal and pharmacological application.FTIR analysis of raw and extracted from leaves, stems, and flowers of Stevia rebaudiana showed a great abundance of alcohols, phenols, aromatic rings, carboxylic acids, ketones, aldehydes, alkanes, ethers, ester, acetylenic as well as olefinic. Heavy metals accumulation in the Stevia rebaudiana from leaves, stems, and flowers is reported. The analysis of sample was carried out by using an Inductively Coupled Plasma Mass-Spectrophotometer (ICP-MS) to analyze the Arsenic (As), Cadmium (Cd), Chromium (Cr), Copper (Cu), Iron (Fe), Magnesium (Mg), plumbum (Pb),Selenium (Se), Zinc (Zn), aluminium (Al), silver (Ag), Cobalt (Co), calcium (Ca),manganese (Mn) and nickel (Ni). The accumulation of heavy metals in leaves, stems, and flowers of Stevia rebaudiana contain fifteen heavy metals below tolerance limit in plant and can be used as food products.